2020
DOI: 10.1096/fj.201902096r
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory‐sensitive CHI3L1 protects nucleus pulposus via AKT3 signaling during intervertebral disc degeneration

Abstract: Intervertebral disc degeneration (IDD) is the main cause of low back pain and the mechanism of which is far from fully revealed. Although inflammation directed nucleus pulposus (NP) extracellular matrix metabolism dysregulation is known to be the main cause of the degeneration process, few is known about the protective factors. Using high‐throughput label‐free proteomics, we found that inflammation‐related autocrine factor Chitinase‐3‐like protein 1 (CHI3L1, or YKL‐40) is highly expressed in the NP cells durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…Consistent with the findings in studies of tumors, we found that M2a macrophages secreted CHI3L1 proteins, thereby promoting ECM degradation. However, we noted that our findings were different from those of Wang et al (34), who recently suggested that CHI3L1 may be a protective factor against IDD. In their experiments, CHI3L1 overexpression or knockdown was performed in NP cells to explore the role of CHI3L1 expression in those cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the findings in studies of tumors, we found that M2a macrophages secreted CHI3L1 proteins, thereby promoting ECM degradation. However, we noted that our findings were different from those of Wang et al (34), who recently suggested that CHI3L1 may be a protective factor against IDD. In their experiments, CHI3L1 overexpression or knockdown was performed in NP cells to explore the role of CHI3L1 expression in those cells.…”
Section: Discussioncontrasting
confidence: 99%
“…51 We also found that C5 and C6 highly expressed genes reflecting protective characteristics (KLF2 and CHI3L1) (Fig. 2e) 54,55 and existed in the dormant stage of proliferation (Fig. 2f).…”
Section: Resultsmentioning
confidence: 69%
“…Based on these preliminary results we posit that CHIL3L1 is one of the key players in driving the healing phenotype of HE-Fibro by expressing proinflammatory and ECM genes together to improve wound repair. Several lines of evidence have previously implicated CHI3L1 in dampening of chronic inflammation [53], promoting M1 macrophage activation [54] and stimulating fibroblast proliferation [55] and ECM remodeling [56]. DEGs analysis on these DFU-Healers vs. other fibroblast clusters revealed some ubiquitous markers ( HIF1A, TNFAIP6 ) that are overexpressed in HE-Fibro cells (Fig 5).…”
Section: Resultsmentioning
confidence: 82%